Self-Care Activities by Patients with Chronic Cardiovascular Morbidities: Explanatory Sequential Facility-Based Mixed Method Study in West Bengal, India - Banerjee, Anagha; Goswami, Pramit; Mandal, Sutapa; Taraphdar, Pranita (National Journal of Community Medicine, 2023)
Background: Chronic cardiovascular morbidities are major public health concern. The objective was to assess awareness and practice of selfcare activities among patients with chronic cardiovascular morbidity in Burdwan Medical College (BMC) and to explore constraints in selfcare practice. Materials & Methods: A facility-based, explanatory sequential, mixed-method study was conducted in Cardiology super-specialty outpatient department of BMC, West Bengal. A calculated sample of 185 patients with chronic cardiovascular morbidity were selected randomly; interviewed with predesigned, pretested schedule (adapted from H-SCALE) for quantitative component. For qualitative component, eight study participants, selected purposively, were interviewed with In-depth-interview guide. Multivariable logistic regression was done to find out predictors of selfcare practice. Thematic inductive analysis was done to explore constraints. Results: 73% study participants were aware about overall selfcare practices; 43.8% performed satisfactory overall selfcare practice. Below secondary level educational status [AOR:0.412, 95% CI (0.178-0.956)] and lower & lower-middle socioeconomic status [AOR:0.063, 95% CI (0.017-0.230)] were found to create negative influence on favourable self-care practice. Thematic analysis revealed false belief, lack of motivation, lack of proper knowledge, emotional disturbances and Covid-19 pandemic impact as major constraints in selfcare practice. Conclusion: Selfcare awareness & practice both are low. Interventions are needed to ensure healthy lifestyle of patients.